Simulasi Perancangan Pembakit Listrik Tenaga Surya Gedung Advance Research Laboratory Universitas Udayana - Bonifacio Tirta Wijata, Marcel (Jurnal Etnik: Ekonomi-Teknik, 2023)
The purpose of this study is to design and evaluate a rooftop PV system that is connected to the PLN grid on Advance Research Laboratory Building rooftop at Udayana University using the PVsyst software. The main factor of this research is the acceleration of the transition to new renewable energy such as PLTS. The overall performance of the solar module is determined by the amount of solar radiation, the type of solar module used, and the orientation of the solar module. PV system which connected to the PLN grid or on-grid is the best choice for commercial-scale renewable energy. In this study, the PVsyst software was used to analyse the maximum power of the installed PV system with a roof surface area of 492 m2. With the specified roof area, 176 solar modules can be installed. The available AC energy produced by PV System is 156.18 MWh/year. The annual horizontal irradiation in Jimbaran, Bali is 2014.6 kWh/m2. The PV system has a Performance Ratio (PR) of 0.785 and a specific energy production of 1604 kWh/kWp/year so that the system is considered to have good feasibility. PV system is able to save electricity consumption of Udayana University Advance Research Laboratory Building during the morning to evening period